2022
DOI: 10.12998/wjcc.v10.i8.2529
|View full text |Cite
|
Sign up to set email alerts
|

Effective response to crizotinib of concurrent KIF5B-MET and MET-CDR2-rearranged non-small cell lung cancer: A case report

Abstract: BACKGROUND Due to the rarity of mesenchymal-epithelial transition factor ( MET ) fusions, the clinical efficacy of crizotinib has only been described in a few patients with MET fusions involving various fusion partners. Herein, we report the clinical response to crizotinib of a patient with advanced poorly differentiated non-small cell carcinoma (NSCLC) having concurrent MET fusions. CASE SUMMARY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…In addition, chemotherapy plus bevacizumab may benefit patients harboring sensitive EGFR mutations and acquired MET amplifications after the failure of EGFR-TKI treatment. In this study, we collected the published cases [14][15][16][17][18][19][20] of patients harboring MET fusions, and the findings cast new light on the role of crizotinib in benefiting these patients. The findings suggested that crizotinib as a single agent can serve as a suitable treatment option for patients harboring primary MET fusions, and combined therapy with crizotinib and EGFR-TKIs could significantly benefit patients with EGFR mutations also harboring acquired MET fusions after the development of resistance to EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, chemotherapy plus bevacizumab may benefit patients harboring sensitive EGFR mutations and acquired MET amplifications after the failure of EGFR-TKI treatment. In this study, we collected the published cases [14][15][16][17][18][19][20] of patients harboring MET fusions, and the findings cast new light on the role of crizotinib in benefiting these patients. The findings suggested that crizotinib as a single agent can serve as a suitable treatment option for patients harboring primary MET fusions, and combined therapy with crizotinib and EGFR-TKIs could significantly benefit patients with EGFR mutations also harboring acquired MET fusions after the development of resistance to EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy is another treatment option for NSCLC patients with MET alterations [11][12][13]. Recently, a series of reports revealed novel detectable alterations of MET, MET fusions, which are involved in the development of lung cancer and exhibit a special response to the given treatment [14][15][16][17][18][19][20]. However, MET fusions are rare in lung cancer, and a systematic analysis of patients harboring this kind of genomic alteration is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The patient had displayed a PR to crizotinib (37). Previous cases have also shown the efficacy of crizotinib in NSCLC patients with MET fusions (68)(69)(70). In September 2018, Zhu et al reported the first case of EGFR-TKI-resistant MET-UBE2H fusion in a patient with LUAD.…”
Section: Met Fusionmentioning
confidence: 97%
“…The most common MET aberrations are gene amplifications and exon 14 splice variants. MET fusion is a rare type of structural rearrangement; nine MET fusion partner genes have been identified, namely: PRKAR2B ( 1 ), KIF5B ( 2 4 ), STARD3NL ( 5 ), CDR2 ( 6 ), UBE2H ( 7 ), HLA-DRB1 ( 8 ), ATXN7L1 ( 9 ), CD47 ( 10 ), and SPECC1L ( 11 ). To date, eight cases of KIF5B -MET gene fusion have been reported in the literature, of which only a few have described the efficacy of crizotinib ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%